INVESTIGATION OF THERMOELECTRIC PROPERTIES IN WURTZITE ZNO MATERIAL: A DENSITY FUNCTIONAL THEORY-BASED APPROACH: INVESTIGASI SIFAT TERMOELEKTRIK PADA MATERIAL ZNO WURTZITE: PENDEKATAN BERBASIS DENSITY FUNCTIONAL THEORY - Vivi Fitriyani; Iwan Sugihartono; Teguh Budi Prayitno (Joint Prosiding IPS dan Seminar Nasional Fisika, 2025)
The investigation of the thermoelectric properties has been conducted through computational simulations on ZnO material with a wurtzite structure. The simulation process began with geometry optimization to obtain a stable material condition using Density Functional Theory (DFT) calculations with Generalized Gradient Approximation (GGA) exchange energy functional. Based on the geometry optimization results, lattice parameters were found to be a = b = 3.286 Å and c = 5.301 Å. Analysis of the thermoelectric values was performed using the semi-classical Boltzmann method. In the simulation, to obtain the Seebeck coefficient, electrical conductivity, and electronic thermal conductivity values, the temperature used was 300 K. Subsequently, these parameters were used to calculate the Thermoelectric efficiency based on the figure of merit (standard thermoelectric efficiency). The calculated figure of merit value was 0.66. This value indicates that the thermoelectric properties of ZnO material with a wurtzite structure are approaching optimal (~1).